Single mode erbium ytterbium-doped fiber laser with multimode pumping - Harun, Sulaiman Wadi; Ahmad, Harith; Lim, E.L.; Alam, S.U.; Richardson, D.J. (World Scientific Publishing, 2010)
An efficient and stable laser action from a double-clad erbium/ytterbium-doped fiber (EYDF) is demonstrated using a fiber Bragg grating at room temperature. The fiber laser operates at wavelength of 1552.3 nm with a slope efficiency of 38% when pumped by multi-mode 915 nm laser diodes. However, the slope efficiency is higher in the EYDF laser configured with double-sided output due to the high splicing loss between the multi-mode combiner and double-clad EYDF. The laser also has a spectral bandwidth of 0.2 nm and signal to noise ratio of more than 25 dB. The threshold power to achieve lasing is measured to be approximately 500 mW for this laser.